IMF Survey, Volume 35, Issue 07. (IMF Survey; IMF Survey ;, 2006)
2006 spring meetings preview; Reform at the IMF: Medium-Term Strategy; Global Financial Stability Report; World Economic Outlook: Oil and imbalances; Globalization and inflation; Puzzle of corporate saving; Profitable investment in Africa.